Impact of Financial literacy on financial performance of smes in mukono district - Tracy Akumu (Uganda Christian University, 2025)
This study examines the impact of financial literacy on the financial performance of youth-led Small and Medium Enterprises (SMEs) within a 5-km radius of Uganda Christian University (UCU) in Mukono District, Uganda. Employing a descriptive research design, data were collected from 71 respondents (77.2% response rate) out of a planned sample of 92, including 51 owners, 14 managers, and 6 holding both roles, across 120 SMEs in retail (40.8%), services (28.2%), agriculture (21.1%), and manufacturing (8.5%). Using structured questionnaires, the study assessed financial literacy components—knowledge, attitudes, and behaviors—and their effects on profitability, liquidity, and access to credit. Findings indicate moderate financial literacy (mean = 3.4/5), with knowledge (mean = 3.59) significantly enhancing profitability by 18% (r = 0.62, p < 0.05), attitudes (mean = 3.29) improving liquidity by 15% (r = 0.51, p < 0.05), and behaviors (mean = 3.17) increasing loan approvals by 25% (r = 0.45, p < 0.05). Multiple regression analysis confirmed a significant positive relationship (R² = 0.568, p < 0.05), with financial attitudes (β = 0.4154, p < 0.001) and knowledge (β = 0.3266, p = 0.004) as the strongest predictors, while behaviors (β = 0.0533, p = 0.566) were less significant in the composite model. Retail SMEs outperformed others due to student-driven demand, while challenges like competition from Kampala, seasonal fluctuations tied to UCU’s academic calendar, and limited training (only 36% of owners trained) were evident. Grounded in Human Capital Theory, Resource-Based Theory, and Financial Socialization Theory, the study rejects the null hypothesis, affirming financial literacy’s role in SME success. Recommendations include community-based budgeting workshops, savings-focused programs, and digital record-keeping training to address knowledge gaps and gender-specific barriers, particularly for women-led SMEs (40.8% of respondents), who face collateral constraints. Future research should explore longitudinal, sector-specific, and gender-focused impacts to enhance SME sustainability in peri-urban contexts like Mukono.